MAXIMIZING THE SHELF LIFE OF MONOXENICALLY PRODUCED CARRIER-BASED AM FUNGAL BIO-INOCULA FOR MAINTAINING ITS LONG-TERM VIABILITY - BERNARD FELINOV, RODRIGUES KIM MARIA, RODRIGUES (Journal of Phytology, 2018)
Arbuscular mycorrhizal (AM) fungi are often applied as bio-inoculants due to their plant growth promoting benefits. The objectives of the present work were to maximize the shelf life of monoxenically produced carrier-based AM fungal bio-inocula of Rhizoglomus intraradices and Funneliformis mosseae. Shelf life of in vitro produced inoculum was studied by assessing the infectivity potential of in vitro produced inocula in an optimum carrier formulation (vermiculite: cow dung powder: wood powder: wood ash in the ratio of 20:8:2:1) during storage at three different temperatures viz., 4 °C, 25 °C and room temperature (RT). The re-germination potential of in vitro produced spores from carrier-based inocula to in vitro conditions was also examined. The in vitro produced inocula stored at 25 °C remained viable up to 6 mo in the organic carrier formulation. 100 % germination was recorded when the spores of both AM species were cultured back to in vitro conditions indicating high viability, and efficiency of the carrier formulation in maintaining vigour of in vitro produced propagules.